2016
DOI: 10.1063/1.4959905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric-field modulation of magnetic parameters on domain structure in MgO/CoFeB

Abstract: We observe magnetic domain structures of MgO/CoFeB with a perpendicular magnetic easy axis under an electric field. The domain structure shows a maze pattern with electric-field dependent isotropic period. The analysis of the period indicates a major role of the electric-field modulation of interfacial magnetic anisotropy for the observation and possible contribution from electric-field modulation of the exchange stiffness constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…In this case, the A change must be ~17% if the EF-induced change in H D obtained here was only caused by the modulation of Δ. However, the EF-induced change in A (or the exchange coupling) is expected to be a few percent at most ( 20 , 21 ). Thus, the EF change in H D was most likely caused by the V G modulation of Dt .…”
Section: Resultsmentioning
confidence: 86%
“…In this case, the A change must be ~17% if the EF-induced change in H D obtained here was only caused by the modulation of Δ. However, the EF-induced change in A (or the exchange coupling) is expected to be a few percent at most ( 20 , 21 ). Thus, the EF change in H D was most likely caused by the V G modulation of Dt .…”
Section: Resultsmentioning
confidence: 86%
“…In Figure a–c, we show the domain configuration dependence on various parameters of (a) K eff , (b) A ex , and (c) M s with d MTJ up to 350 nm, using the typical values reported in similar structure. [ 23,24,30,35,43 ] Overall, the FL splits from single domain to two or more domains with increasing d MTJ . To obtain multi‐domain structure in smaller p‐MTJs, the FL properties should be carefully tuned.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported modification of exchange stiffness by applying Electric field 44 which is not considered in our model. However, a positive (negative) electric field will increase (decrease) the exchange stiffness which will enable easy transformation from skyrmion to ferromagnetic (ferromagnetic to skyrmion) state which can be understood from the energy profile plotted in Fig.…”
Section: Methodsmentioning
confidence: 99%